Los modelos del proceso de la escritura - Santana, Begoña (1985)
The present paper intends to offer a general view of the actual state of the theories on the process of writing. In order to do so, the evolution of the assumptions underlying the models of writing is exposed. These models can be classified on the basis of three distinctive stages in three main groups: translation models, stage models and the current cognitive models. In second place, some factors which have contributed to the appearance of these last models, as well as some of their objetives and requirements are indicated. Next, the model developed by Flower and Hayes (1979, 1980, 1981 a and b) is exposed as a prototypical example of this perspectives. Finally, a series of conclusions about the evolution of the models, about the main common characteristics shared by the cognitive models, and about current tendencies in the elaboration of these theories are offered